Quatro novos registros da fauna flebotomínica do gênero Lutzomyia França (Diptera: Psychodidae, Phlebotominae) do distrito rural de Brejo do Mutambal, Varzelândia, MG - Andrade, Andrey J.; Andrade, Mateus R.; Barata, Ricardo A.; Pinto, Mara C. [UNESP]; Dias, Edelberto S.; Eiras, Alvaro E. (Entomological Soc Brasil, 2007)
During April and May 2006, experiments were carried out in Brejo do Mutambal, Varzelandia Town, Minas Gerais State, to evaluate the attractiveness of phlebotomine sandflies to CDC light traps, baited with kairomones. of the 19 species of Lutzomyia already registered for the region, L. lutziana (Costa Lima), L. longipennis (Barreto), L. goiana (Martins, Falcao & Silva) and L. brasiliensis (Costa Lima) were recorded for the first time, thus increasing the diversity of phlebotomine sandflies fauna in this area to 23 species. The new registered species and distribution are shown and discussed herein.
Four new records of the phlebotominic fauna of the genus Lutzomyia franqa (Diptera : Psychodidae, Phlebotominae) of the rural district of Brejo do Mutambal, Varzelandia, state of Minas Gerais, Brazil
Keywords: Lutzomyia lutziana; L. longipennis; L. goiana; L. brasiliensis; first record